2014
DOI: 10.3892/or.2014.3314
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a cisplatin-resistant human osteosarcoma cell line

Abstract: Abstract. The aim of the present study was to establish a new cisplatin-resistant human osteosarcoma cell line and investigate its biological characteristics. The human osteosarcoma cell line SOSP-9607 was exposed to cisplatin by stepwisely increasing the concentrations in the medium to select for the drug-resistant subline, SOSP-9607/CDDP cells. The morphological features were observed using inverted microscopy. The growth curves of SOSP-9607 and SOSP-9607/CDDP cells were drawn to calculate the doubling time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…In our experiments, we found that the proliferation ability of the resistant cells MG63/PDT and HOS/PDT was weaker than that of their primary MG63 and HOS cells, respectively. The results are similar to those found in the CDDP resistant osteosarcoma cells SOSP-9607/CDDP ( 38 ). The slow proliferation of the resistant cells may be caused by the increased quiescent cells ( 16 ).…”
Section: Discussionsupporting
confidence: 88%
“…In our experiments, we found that the proliferation ability of the resistant cells MG63/PDT and HOS/PDT was weaker than that of their primary MG63 and HOS cells, respectively. The results are similar to those found in the CDDP resistant osteosarcoma cells SOSP-9607/CDDP ( 38 ). The slow proliferation of the resistant cells may be caused by the increased quiescent cells ( 16 ).…”
Section: Discussionsupporting
confidence: 88%
“…Another well-documented mechanism underlying CDDP resistance in cancer cells is the increased efflux of CDDP by the ABC transporter protein family, including MDR1/ABCB1 (P-glycoprotein), MRP1/ABCC1 and BCRP/ABCG2 (20,29). However, we failed to detect the dysregulated expression of these genes in CDDP-resistant cells following pretreatment with ZOL.…”
Section: A B a Bcontrasting
confidence: 47%
“…It was identified that upregulation of HIPK2 inhibits cell metastasis and suppresses cell viability during cisplatin treatment, implicating a potential application of HIPK2 in ESCC therapy. (17). After continuous exposure to cisplatin for 2 days, the medium was replaced with a fresh cisplatin free medium until the surviving cells recovered favorably.…”
Section: Introductionmentioning
confidence: 99%